DESIGNING MOBILE-BASED DECISION SUPPORT SYSTEM FOR DETERMINING POLICE OFFICE LOCATIONS USING FORWARD CHAINING METHOD - Melda Agarina; Agung Nugroho Menggala Putra; Sutedi Sutedi (Proceeding International Conference on Information Technology and Business, 2018)
A number of people are recently increasing so that some places are needed to be built and used for them. One of the needed places is the police headquarter. The police headquarter is the social facility used to improve the security in the social life. The police headquarter is recently accessible so that the crime rates in the certain region are reduced. The other factors determining the feasibility of the locations to build the police headquarter are a number of people, a level of high vulnerability, a number of schools, the ethnic groups, the new regions, and the inter-provincial passing area. The problem statement of this research was that the police headquarter locations were not well-distributed. To solve this problem, the mobile-based decision support system was built by using the forward chaining method for determining the police headquarter location. This system consisted of 16 criteria that helped provide feasibility to establish the police headquarter. The criteria were safe and rarely-conflict, highly potential for conflicts, highly public order insecurity, highly public order security, inter-provincial passing area, non-interprovincial passing area, recent established regions, non-recent established regions, the number of people around 3000, the number of people under 3000, the number of schools over 10 schools, the number of schools under 10 schools, the number of social community over 50 people, the rarely number of social organizations, the number of ethnic groups reaching 20-40, and the number of ethnic groups under 20-40. The result of this research showed that this system was able to facilitate the police to determine the police headquarter locations using the rule so that the decision was created whether the police headquarter was able to be established in certain districts and beneficial for the people.Keywords: Decision Support System, Forward Chaining, Mobile